Pluralizando masculinidades performativas: uma pesquisa com jovens em cumprimento de medidas socioeducativas - Oliveira, João Victor (Universidade Federal de São Carlos, 2023)
This work is situated at the interface of major contemporary sociological debates: youth, masculinity, and the world of crime. Aiming to explore what I have referred to as performative masculinities among young individuals undergoing socio-educational measures due to involvement in crime, I problematize specific dimensions of each of these debates. Starting from an ethnographic study focused on participant observation of the routine activities of young individuals who were undergoing socio-educational measures at Salesianos, witch is the institution that coordinates and promotes open-ended measures in the city of São Carlos – SP, I have organized a typology consisting of four types of performative masculinities related to signs of: I) humility and conduct, II) bravatas and bragging, III) family, responsibility, and gratitude and IV) violence, virility, and pride.
Pluralizing performative masculinities: a study with youth in socioeducational measures
Keywords: Mundo do crime; Masculinidades performativas; Medidas socioeducativas; Juventudes; CIENCIAS HUMANAS::SOCIOLOGIA